Bone morphogenetic protein-9 increases the functional expression of organic anion transporting polypeptide 1a4 at the blood–brain barrier via the activin receptor-like kinase-1 receptor - Abdullahi, Wazir (J Cereb Blood Flow Metab, 2017)
Targeting uptake transporters such as organic anion transporting polypeptide 1a4 (Oatp1a4) at the blood–brain barrier (BBB) can facilitate central nervous system (CNS) drug delivery. Effective blood-to-brain drug transport via this strategy requires characterization of mechanisms that modulate BBB transporter expression and/or activity. Here, we show that activation of activin receptor-like kinase (ALK)-1 using bone morphogenetic protein (BMP)-9 increases Oatp1a4 protein expression in rat brain microvessels in vivo. These data indicate that targeting ALK1 signaling with BMP-9 modulates BBB Oatp1a4 expression, presenting a unique opportunity to optimize drug delivery and improve pharmacotherapy for CNS diseases.